2012
DOI: 10.1371/journal.pone.0046325
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide and Locus Specific Alterations in CDC73/HRPT2-Mutated Parathyroid Tumors

Abstract: Mutations in the hyperparathyroidism type 2 (HRPT2/CDC73) gene and alterations in the parafibromin protein have been established in the majority of parathyroid carcinomas and in subsets of parathyroid adenomas. While it is known that CDC73-mutated parathyroid tumors display specific gene expression changes compared to CDC73 wild-type cases, the molecular cytogenetic profile in CDC73-mutated cases compared to unselected adenomas (with an expected very low frequency of CDC73 mutations) remains unknown. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…In parathyroid tumors, a rare, homozygous activating β-catenin (CTNNB1) mutation has been demonstrated for a few cases, suggesting a role for β-catenin in parathyroid tumorigenesis. 36 Subsequent studies regarding β-catenin expression in parathyroid tumors revealed discordant findings regarding sub-cellular is in agreement with our own and others' previous reports, 15,16 further excluding promoter hypermethylation as an inactivation mechanism. In addition, the methylation profile of the MEN1 and CDC73 mutated cases did not reveal any statistically significant differences.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In parathyroid tumors, a rare, homozygous activating β-catenin (CTNNB1) mutation has been demonstrated for a few cases, suggesting a role for β-catenin in parathyroid tumorigenesis. 36 Subsequent studies regarding β-catenin expression in parathyroid tumors revealed discordant findings regarding sub-cellular is in agreement with our own and others' previous reports, 15,16 further excluding promoter hypermethylation as an inactivation mechanism. In addition, the methylation profile of the MEN1 and CDC73 mutated cases did not reveal any statistically significant differences.…”
Section: Discussionsupporting
confidence: 90%
“…Although tumor representativity was not performed for these cases, previous DNA analyses from these samples using array-comparative genomic hybridization (a-CGH) visualized gross chromosomal alterations in agreement with previous publications regarding parathyroid carcinomas. 16 In addition, paraffin-embedded tissue specimens from metastatic cases have shown high tumor cell proportion in comparison to surrounding lung tissue, suggesting a high tumorto-normal tissue proportion. 51 In summary, this study suggests a role of aberrant promoter methylation for APC 1A, RASSF1A, and β-catenin genes in the molecular pathogenesis of a subset of parathyroid tumors and may indicate the disruption of multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported in a pleomorphic xanthoastrocytoma (Koelsche et al 2013). The patient, a 16-year-old male with unknown family history of the disease and lost to follow-up, carries a constitutional W45X mutation of CDC73 together with a second W30X mutation of CDC73 in T1 (Sulaiman et al 2012).…”
Section: Dear Editormentioning
confidence: 91%